2019
DOI: 10.3389/fcimb.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the in vitro, ex vivo, and in vivo Efficacy of the Antimicrobial Peptide DPK-060 Used for Topical Treatment

Abstract: Antimicrobial peptides, also known as host defense peptides, have recently emerged as a promising new category of therapeutic agents for the treatment of infectious diseases. This study evaluated the preclinical in vitro, ex vivo , and in vivo antimicrobial activity, as well as the potential to cause skin irritation, of human kininogen-derived antimicrobial peptide DPK-060 in different formulations designed for topical delivery. We found that DPK-060 formulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Very surprisingly, Håkansson et al loaded DPK-060 into three different nanosystems: lipid nanocapsules (LNCs), nanocubes, and polaxamer gels compared to the parent DPK-060 peptide in acetate buffer. No enhanced effect was found when encapsulating DPK-060 in any of the formulations, except when including AMP in polaxamer gels [199]. This points out the need for a specific optimization of the carrier for a given peptide through activity and toxicity testing.…”
Section: Smart Nanomaterialsmentioning
confidence: 90%
“…Very surprisingly, Håkansson et al loaded DPK-060 into three different nanosystems: lipid nanocapsules (LNCs), nanocubes, and polaxamer gels compared to the parent DPK-060 peptide in acetate buffer. No enhanced effect was found when encapsulating DPK-060 in any of the formulations, except when including AMP in polaxamer gels [199]. This points out the need for a specific optimization of the carrier for a given peptide through activity and toxicity testing.…”
Section: Smart Nanomaterialsmentioning
confidence: 90%
“…The results showed that RADA16 peptide hydrogels were able to release active TGF-β1 growth factor and significantly influenced the proliferation of stem cells [168]. including AMP in polaxamer gels [169]. This point out the need for a specific optimization of the carrier for a given peptide, through thorough activity and toxicity testing.…”
Section: Smart Nanomaterialsmentioning
confidence: 97%
“…Pexiganan has been evaluated as a topical cream in two phase III clinical trials for the treatment of mild infections in diabetic foot ulcers (NCT01590758, NCT01594762) and additional clinical studies are reportedly planned in cSSSI including surgical wounds, burns, and decubitus ulcers [69]. Similarly to omiganan and pexiganan, DPK-060 (structurally derived from human protein kininogen) also displays a broad spectrum of antimicrobial actions [70][71][72]. The efficacy of DPK-060 ointment has been studied in clinical phase II trials in the treatment of infections in atopic dermatitis (NCT01522391) [72] and acute external otitis (NCT01447017).…”
Section: Therapeutic Applications Of Ampsmentioning
confidence: 99%